2007
DOI: 10.1111/j.1469-8986.2007.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Age effects to negative arousal differ for self‐report and electrodermal activity

Abstract: Affective processing and emotional experience may change with age. Because findings of age differences in affective experiences are mixed even in studies using standardized stimuli, this study assessed age differences along gradual increases in negative arousal. Younger (20-30 years) and older (70-80 years) healthy adults (n=78) viewed 110 neutral to negative pictures (IAPS) while intensity ratings and electrodermal activity were recorded. Results showed that age had opposite effects on intensity ratings and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 26 publications
10
63
0
2
Order By: Relevance
“…Previous research reveals age-related declines on measures of visual perception (Bennet, et al, 2007; Flaubert, 2002; Habak & Faubert, 2000) and visual search (Madden, 2007). Moreover, older adults also show weaker physiological responses to emotional stimuli (Gavazzeni, et al, 2008; Levenson, et al, 1991), suggesting that emotional arousal may have less of an influence on attention in later age. Thus one possible hypothesis was that these age-related declines would interfere with emotion-induced attention biases to subsequently presented stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reveals age-related declines on measures of visual perception (Bennet, et al, 2007; Flaubert, 2002; Habak & Faubert, 2000) and visual search (Madden, 2007). Moreover, older adults also show weaker physiological responses to emotional stimuli (Gavazzeni, et al, 2008; Levenson, et al, 1991), suggesting that emotional arousal may have less of an influence on attention in later age. Thus one possible hypothesis was that these age-related declines would interfere with emotion-induced attention biases to subsequently presented stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ability to detect perceptual contrasts (Bennet, Sekuler, & Sekuler, 2007; Flaubert, 2002; Habak & Faubert, 2000) and the targets in visual search tasks (Madden, 2007) declines. Moreover, physiological responses to emotional stimuli also diminish with age (Gavazzeni, Wiens, & Fischer, 2008; Levenson, Carstensen, Friesen, & Ekman, 1991), suggesting that the impact of emotion on attention in older adults may also decline. Nevertheless, there is evidence that emotionally arousing stimuli continue to attract increased attention in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, older adults generally show attenuated electrodermal activity (Gavazzeni, Wiens, & Fischer, 2008), which might lead to a main effect of age on the physiological response.…”
Section: Study Design and Hypothesesmentioning
confidence: 99%
“…Given that it has previously been reported that older adults rate emotional images as less arousing (Grühn and Scheibe, 2008;Pôrto et al, 2011) and show a reduced SCR in response to arousal (Gavazzeni et al, 2008), we predicted that the older adults would show less BOLD modulation than the young group in response to increasing levels of arousal.…”
Section: Introductionmentioning
confidence: 98%
“…There have been conflicting reports of older adults' autonomic response to emotional arousal however. Older adults have been found to show less increases in the skin conductance response (SCR) to highly-arousing negative images compared with younger adults, despite higher self-reports of arousal levels (Gavazzeni et al, 2008). This would imply that aging is associated with a decreased autonomic response to emotional arousal; however, other studies have contradicted this result (Denburg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%